2016
DOI: 10.1515/intag-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected parameters of biomass and coal

Abstract: As a fuel, biomass differs in its properties from fossil fuels and acquisition thereof for energy purposes is limited; hence, the ongoing search for new bioenergetically useful plants. The article presents the results of physical and chemical analyses of seven species of perennial grasses: tall wheatgrass, tall wheatgrass ‘Bamar’, brome grass, tall fescue ecotype, reed canary grass, giant miscanthus, and sorghum. The research involved technical and elemental analysis as well as analysis of the ash composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…(Obernberger et al, 2006). The results of the experiment in this study have shown that the poplar and willow biomass contains lower values andfrom this perspective -these are better fuels than the other source of biomass Lalak et al, 2016;Obernberger et al, 2006) and bituminous coal (Cuiping et al, 2004).…”
Section: Species (A) Soil Enrichment (B)mentioning
confidence: 60%
See 1 more Smart Citation
“…(Obernberger et al, 2006). The results of the experiment in this study have shown that the poplar and willow biomass contains lower values andfrom this perspective -these are better fuels than the other source of biomass Lalak et al, 2016;Obernberger et al, 2006) and bituminous coal (Cuiping et al, 2004).…”
Section: Species (A) Soil Enrichment (B)mentioning
confidence: 60%
“…The SRWCs biomass can contain several times less ash than the straw or grass biomass (Greenhalf et al, 2012;Lalak et al, 2016). Still, compared to coal, ash content in woody biomass can be up to a dozen times lower (Bowen and Irwin, 2008;Dincer and Zamfirescu, 2014).…”
Section: Species (A) Soil Enrichment (B)mentioning
confidence: 99%
“…The high carbon content translates into increased energy parameters in the form of GCV and NCV for the studied biomass. M. × rotundifolia L., on the other hand, showed a similar carbon content to larch needles [41], tall fescue ecotype, sorghum [53], M. spicata L., and M. crispa L., and have a similar carbon content to apple tree leaves [54], Sudan grass [48], reed canary grass [53], and Virginia mallow [14]. It should be noted that the tested mint has a higher carbon content also in relation to Spire-mint, and the difference in relation to M. × piperita L. var.…”
Section: Discussionmentioning
confidence: 87%
“…Similar carbon content was found in Mentha × piperita L. var. citrata Ehrh.-'Bergamot' (the highest content among the tested plants) in relation to oak tree leaves [49], block wood [48], and Miscanthus [53]. The high carbon content translates into increased energy parameters in the form of GCV and NCV for the studied biomass.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation